Remote methods of research assessment of the impact of agricultural economic processes on the environmental destruction of the territory - Trysnyuk, Taras V. (Kyiv National University of Construction and Architecture, 2023)
The research is about solving the problem of assessing the impact of agricultural processes on the environmental safety of territories. The research was carried out on the selection, uploading and processing of data from the aerial survey of the area. High-quality multispectral images of the study areas were selected in accordance with the time-related thematic tasks of aerospace research of agricultural plots. With the help of Google Earth Engine platform, JavaScript programming language, ENVI and ArcMap software complexes, segmentation of the image of space images was carried out on these images. Each of them has its own normalized color scale, and highlights certain objects with different colors. To improve the visualization of differences in images, the classification of index images using the Isodata method was studied.An Agrocontrol module for automated deciphering of agricultural was developed. The module allows to select agricultural land with further vectorization and the possibility of creating a geodatabase automatically. Based on results, preliminary cartographic models of the studied territories were created with the indication of land plots that are dangerous for the ecological state of the region and require more careful consideration.At the stage of practical research, an analysis of the received data, based on the agricultural holding "Mriya", was carried out on the scheme of crop rotation, hybrids of grain crops grown on the territory of the plots, the types and amount of fertilizers used, as well as the volume of the harvest for the last 5 years. This made it possible to prove the correlation between the chemical composition of the used fertilizers and the corresponding exceedances of the MPC norms of the soil samples chemical composition.